Berberine Ameliorates Diabetes-Associated Cognitive Decline through Modulation of Aberrant Inflammation Response and Insulin Signaling Pathway in DM Rats - Chen, Qingjie; Mo, Ran; Wu, Ninghua; Zou, Xin; Shi, Cai; Gong, Jing; Li, Jingbin; Fang, Ke; Wang, Dingkun; Yang, Deshen; Wang, Kaifu; Chen, Juan (Frontiers in Pharmacology, 2017)
Background Memory-impairment was one of the common characteristics in patients with diabetes mellitus. The release of chronic inflammation mediators and insulin resistance in diabetic brain gave rise to the generation of toxic factor Aβ42 which was the marker of Alzheimer's disease (AD). In addition, the impairment of memory in diabetes mellitus was also correlated predominantly with uptake/metabolism of glucose in medial prefrontal cortex (mPFC). Previously, anti-inflammation and hypoglycemic effects of berberine have been described in peripheral tissues. For better understanding the effects of berberine on cognitive action in diabetics, we investigated the functions of berberine involved in anti-inflammation and ameliorating insulin resistance in prefrontal cortex of diabetic rats. Methods Intragastric administration of berberine (187.5mg/Kg/d) was used in diabetic rats. Fear-condition assay was applied for cognitive assessment, and relative protein expressions were detected by western-blot. The glucose uptake in prefrontal cortex of diabetic rats was tested by Positron-Emission Tomography (PET) imaging. The levels of inflammation mediators were determined by commercial ELISA kits. Results The inflammation mediator release and insulin resistance in the mPFC of diabetic rats was inhibited by BBR. The activation of PI3K/Akt/mTOR and MAPK signaling pathway, as well as two novel isoforms PKCη and PKCε and the translocation of NF-κB in neuron were also down-regulated by berberine; furthermore, the neuron specific glucose transporter GLUT3 was remarkably augmented by 2-3 times when compared with diabetic group; meanwhile, berberine also promoted glucose uptake in the brain. Additionally berberine decreased the expressions of amyloid precursor protein (APP) and BACE-1, and the production of oligomeric Aβ42. Finally, it accelerates the reinforcement of the information and ameliorates cognitive impairment. Conclusion Berberine inhibited the activation of inflammation pathway and insulin resistance in the mPFC of diabetic rats. Finally, it improved the lesion of cognition in diabetic rats.